Abdominal compartment syndrome. Interesting aspects. - Nicolás Rubio Silveira; Carlos Echevarría del Risco; Kadel Canino Cereijo; Katia García Paneca (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
The management of the abdominal compartiment syndrome is still a controversial point nowadays. Its early diagnosis and treatment constitute a challenge for surgeons and physicians at the intensive care unit who have to face these cases . The physiopathologic changes that can occur can lead to the patients death, constituting pulmonary thromboembolism and multiorgan failure the principal causes of death. This paper presents the principal clinical parameters and technical procedures for its diagnosis and treatment with the aim of diminishing its morbi-mortality raits in our hospitals